Comparative Study of Biochemical and PCR Tests in the Detection of Mycoplasma Contaminations of Genital Secretions of Infertile Women and Men - Elnaz Hamedi; Babak Kheirkhah; Kumars Amini (Bihdād, 2018)
Introduction: Mycoplasma are from cell culture the main polluters. Mycoplasma hominis is one of the most important human mycoplasmas are associated with infections of the genitourinary system in women and men. The aim of this study compare methods of detection of mycoplasma contamination in the genital secretions of men and women referring to infertility center is Kerman. Materials and Methods: This descriptive cross-sectional study was performed on 100 women and 100 infertile men referred to Kerman Infertility Center during 6 months. Samples that were sent to the laboratory in the PPLO Broth filter 0.45 micrometers were passed and in accordance with the instructions, they were cultured in PPLO solid liquid and solid media and stored at 37 ° C,  Co2 incubator. After the extraction of DNA by using PCR method and especial primers, the species and genus of Mycoplasma hominis were determined and studied. Findings: Of the 200 samples examined by culture method, 17.5% of mycoplasma colonies were positive and using biochemical tests were mycoplasma hominis 6%. By PCR method, 44% of samples were infected with mycoplasma and 16.5% contaminated they were mycoplasma hominis. Discussion & Conclusion: The results of this study show that PCR is a sensitive and rapid method for detecting Mycoplasma huminis in infertile women and men.